-1

I have to rely only on SD+ rules

I use the Logic Book.

Show that the following is valid in SD+

Derive Y=Z

1.~Y-> ~Z. Assume

2.~Z->~X. Assume

3~X->~Y. Assume

I got Z->Y but am stumped on getting Y->Z

I tried everything.

I request any help or hints in finishing it.

0

Use the contrapositive. Y->X, X->Z, therefore Y->Z. (you can show this follows by assuming Y and using modus ponens).

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.